Rift Structure and Sediment Infill of Hyperextended Continental Crust: Insights From 3D Seismic and Well Data (Xisha Trough, South China Sea). Issue 5 (6th May 2020) - Lei, Chao; Alves, Tiago M.; Ren, Jianye; Tong, Chuanxin
Abstract: Three‐dimensional seismic and well data from the deepwater Xisha Trough are used to investigate the rift structure and sediment infill of a region formed adjacently to the initial oceanic ridge of the South China Sea (SCS). The high‐quality data permitted a detailed analysis of features such as (1) detachment faults soling out at the Moho, (2) rotated and thinned continental blocks covered by thick sediment, and (3) changes in the location of basin depocenters resulting from detachment faulting. During the continental rifting phase (Eocene to earliest Oligocene), faulting was broadly distributed in the Xisha Trough and resulted in the generation of isolated grabens/half grabens filled by proximal sediment sources. During continental breakup in the Northwest Ocean Sector of SCS (Oligocene), extension became restricted to a narrow region where highly tilted continental blocks and thin crust were formed. Sediment was, at that time, fed to distal depocenters, which are presently bounded by listric faults rooted in a basal detachment. Later in a second stage (early Miocene), synchronously with continental breakup in the Southwest Ocean Sector of the SCS, the study area was blanketed by thick sediment. During the two continental breakup events, the hyperextended Xisha Trough was affected by closely spaced, small‐scale faults rather than large basement‐related structures. Our study highlights the effect of continental breakup as a way to broaden sediment influx from multiple sources into deepwater basins. As a corollary, this work recognizes two distinct breakup sequences in the Xisha Trough and concludes on their geodynamic significance to the SCS. Key Points: The continental crust in the Xisha Trough was thinned by a detachment fault system Post‐rift units were moderately faulted within two distinct breakup sequences Sediment influx changed from proximal to distal and from transverse to axial, with progressive crustal extension